Ответ:
Пошаговое объяснение:
3 . 1) 5,6 - 3(2 - 0,4х) = 0,4(4х + 1); ( x + 2 )/9 = ( x - 3 )/2 ; 5,6 - 6 +1,2х = 1,6х + 0,4 ; 2( x + 2 ) = 9( x - 3 ) ;
1,6х - 1,2х = 5,6 - 6 - 0,4 ; 2x + 4 = 9x - 27 ;
0,4х = - 0,8 ; 9x - 2x =4 + 27 ;
х = - 0,8 : 0,4 ; 7x = 31 ;
х = 2 . x = 31 : 7 ; x = 4 3/7 .
В - дь : 1) х = 2 ; 2) x = 4 3/7 .
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
3 . 1) 5,6 - 3(2 - 0,4х) = 0,4(4х + 1); ( x + 2 )/9 = ( x - 3 )/2 ; 5,6 - 6 +1,2х = 1,6х + 0,4 ; 2( x + 2 ) = 9( x - 3 ) ;
1,6х - 1,2х = 5,6 - 6 - 0,4 ; 2x + 4 = 9x - 27 ;
0,4х = - 0,8 ; 9x - 2x =4 + 27 ;
х = - 0,8 : 0,4 ; 7x = 31 ;
х = 2 . x = 31 : 7 ; x = 4 3/7 .
В - дь : 1) х = 2 ; 2) x = 4 3/7 .